An exploratory study of children with caries and its relationship to SARS-CoV-2 - Débora Heloísa Silva de BRITO; Thaysa Gomes Ferreira Tenório dos SANTOS; Juliane Rolim de LAVÔR; Mabel Cristina Paiva Machado da SILVA; Natália Maria Velozo dos SANTOS; Larissa Mayara Costa de PAULA; Monica Vilela HEIMER; Arnaldo de França CALDAS JÚNIOR; Aronita ROSENBLATT (Sociedade Brasileira de Pesquisa Odontológica, 2023)
Abstract This exploratory study investigated whether children with dental decay were more likely to have COVID-19 than those without caries. The children underwent dental inspection and blood collection for detection of SARS-CoV-2 antibodies. Fifty-four children aged 6 to 9 years participated in the survey, which was conducted between March and June 2020 in the municipality of Ipojuca, Pernambuco, Brazil. The diagnosis of caries was performed using the dmft and DMFT indices. Parents reported signs and symptoms of sickness in their children during this period. The serology test aimed to verify the immune response of the children to coronavirus by detecting IgM/IgG antibodies. Statistical analyses were performed at P < 0.05. The majority of the children presented caries (68.5%). Of the nine children who tested positive for COVID-19 (16.7%), eight presented IgG antibodies to the virus, and only one had IgG and IgM antibodies to SARS-CoV2. Children who tested positive for SARS-CoV-2 had a higher percentage of caries lesions than those who tested negative for SARS-CoV-2 (77.8% vs 65.9%), but this difference was not statistically significant.